(untitled) - Dyson, Simon (New York, 2006)
Social Theory and Applied Health Research provides an accessible assessment of dilemmas facing social researchers in trying to make sense of the world of health care. It links theory and method by presenting an account of how reflection can help amend, complement and strengthen a practical research strategy. Using clear diagrams, tables and examples of recent research, the book illustrates principles from social theory from a range of applied research studies
Keywords: Medical care,Delivery of Health Care,Chăm sóc sức khỏe sinh sản,Chăm sóc y tế; Research,Methodology,Nghiên cứu,Phương pháp